Effects of a carbon monoxide-dominant gas mixture on the explosion and flame propagation behaviors of methane in air. (March 2019) - Luo, Zhenmin; Liu, Litao; Cheng, Fangming; Wang, Tao; Su, Bin; Zhang, Jiang; Gao, Shuaishuai; Wang, Chao
Abstract: This work aimed to experimentally evaluate the effects of a carbon monoxide-dominant gas mixture on the explosion characteristics of methane in air and report the results of an experimental study on explosion pressure measurement in closed vessel deflagration for a carbon monoxide-dominant gas mixture over its entire flammable range. Experiments were performed in a 20-L spherical explosion tank with a quartz glass window 110 mm in diameter using an electric spark (1 J) as the ignition source. All experiments were conducted at room temperature and at ambient pressure, with a relative humidity ranging from 52 to 73%. The peak explosion pressure ( P max ), maximum pressure rise rate (( dp/dt ) max ), and gas deflagration index ( K G ) were observed and analyzed. The flame propagation behavior in the initial stage was recorded using a high-speed camera. The spherical outward flame front was determined on the basis of a canny method, from which the maximum flame propagation speed ( S n ) was calculated. The results indicated that the existence of the mixture had a significant effect on the flame propagation of CH4 -air and increased its explosion risk. As the volume fraction of the mixed gas increases, the P max, ( dp/dt ) max, K G and S n of the fuel-lean CH4 -air mixture (7% CH4 -air mixture) increase nonlinearly. In contrast, addition of the mixed gas negatively affected the fuel-rich mixture (11% CH4 -air mixture), exhibiting a decreasing trend. Under stoichiometric conditions (9.5% CH4 -air mixture), the mixed gas slightly lowered P max, ( dp/dt ) max, K G, and S n. The P max of CH4 -air mixtures at volume fractions of 7%, 9.5%, and 11% were 5.4, 6.9, and 6.8 bar, respectively. The S n of CH4 -air mixtures at volume fractions of 7%, 9.5%, and 11% were 1.2 m/s, 2.0 m/s, and 1.8 m/s, respectively. The outcome of the study is comprehensive data that quantify the dependency of explosion severity parameters on the gas concentration. In the storage and transportation of flammable gases, the information is required to quantify the potential severity of an explosion, design vessels able to withstand an explosion and design explosion safety measures for installations handling this gas. Highlights: The addition effect of carbon monoxide-dominant gas mixture on CH4 -air explosion was examined. The Pmax, (dp/dt)max, and KG of the fuel-lean CH4 -air mixture, the stoichiometric conditions and fuel-rich mixture were systematically investigated. The maximum flame propagation speed in the initial stage was determined by using image processing technology.